Gangguan Wicara Pada Anak Umur 16 Tahun: Suatu Kajian Neuro-Morfologi - Johan, Mhd; Rudianto, Gaguk (eScience Humanity Journal, 2025)
The purpose of this study is to find disturbances in the respondents' speech in producing morphemes and phonemes. In developing the thinking of writing this study, the author used the theory of Ingram, Nida in Johan, Mubarak, Satria, Yunisa, Lawi, Yunaspi. In collecting data, the author used the method of involved observation to the conversation initiated by Sudaryanto, in addition, the author also used the fishing technique initiated by Nadra. In obtaining data, the author was actively involved in fishing for respondents to talk, then the author analyzed the data using the distribution method, and supported by the Direct Element Sharing Technique, the Lesion Technique, the Addition Technique, and the Replacement Technique. Then six data and seven problems were obtained. The problems were the problem of omission and the problem of adding or adding phonemes. After that, among the problems that arose, various meanings arose from the problem. The problems include the emergence of differences in meaning or giving rise to new meanings in the word, in addition, words that are meaningless appeared. After that, words appeared whose meanings resembled the original meanings.